Characteristics of health behaviours and health status indicators among pregnant women in Slovenia - Kek, Tina (Zdravniški vestnik, 2017)
Pregnancy is a period when women reconsider their own health and health related behaviour for the sake of their future child. Along with their health providers, they are faced with a number of risk assessments and decisions, which become far more complex as their effect on two organisms rather than one is at play. This paper provides an overview of possible associations between self-reported health status, health behaviours and socio-demographics during pregnancy. Methods: Study data were obtained from the case-control research project Analysis of folate metabolism biomarkers in the risk assessment for neural tube defects, orofacial clefts and congenital heart defects, which recruited participants from May 2013 to September 2015. Questionnaires about maternal health, health related behaviour and socio-demographic characteristics were completed by 450 women. The data include pregnancies from the 1980s to 2015. Results: We observed that younger and less educated women more frequently reported positive smoking status during pregnancy, while higher prevalence of folate/multivitamin supplementation was found among more educated, older and nulliparous women. There was a U-shaped distribution of medication intake (over-the-counter and prescribed) with respect to educational level, with the highest intake in mothers with a masters/PhD degree and among those that completed elementary school. Higher medication usage was also reported among older women. With increasing maternal age there was an increase in medication intake, folate/multivitamin intake, as well as incidence of gestational diabetes over the studied time period, with the highest frequencies occurring in later decades. A higher incidence of chronic diseases was observed in a group of multiparous women than among monoparous women. Conclusions: Considerable socio-demographic disparities exist in health-related behaviour among pregnant women. Improved public health campaigns and individual health care counselling are needed to address specific requirements of socio-demographic groups at higher risks of adverse pregnancy outcomes.
Keywords: drug; human pregnancy; navade; Nosečnost; socialno demografski dejavniki; Zdravila; Zdravje; zdravje nosečnic